2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--20051
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study on the Contextual Challenges and Barriers of Introducing Sustainability to First-Year Engineering Students

Abstract: Engineer, M. Sc. and PhD candidate (Old Dominion University), with 9+ years of experience in business and government environments. Experience with STEM related initiatives both at the k-12 level and Higher Education; with main focus on strategies for improving student engagement and performance. Additional experience working with Faculty on the integration of Instructional Technologies in the classroom. Major strengths in innovative problem solving; modeling and simulation (mainly for business analysis and gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…However, the study also indicated that disciplinary communication tools need to be adjusted to include another discipline's members in the conversations. Additionally, some case studies reveal an interest in improving engineering design education for undergraduate students, introducing interdisciplinary design and sustainability [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, the study also indicated that disciplinary communication tools need to be adjusted to include another discipline's members in the conversations. Additionally, some case studies reveal an interest in improving engineering design education for undergraduate students, introducing interdisciplinary design and sustainability [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%